Awareness of Halal Certification Ownership Among Micro, Small, and Medium Enterprises (MSMEs) in Iringmulyo, East Metro - Apriliana, Sinta; Mustofa, Ulul Azmi (Halal Science, 2025)
Halal certification serves as a formal assurance that products comply with Islamic law, making it increasingly important in Muslim-majority markets, such as Indonesia. However, many Micro, Small, and Medium Enterprises (MSMEs) still lack certification due to limited awareness and procedural challenges. This study aims to assess the level of awareness and understanding of halal certification among MSMEs in Iringmulyo, East Metro, and identify barriers to certification uptake. A qualitative descriptive approach was employed, utilizing field research methods that included interviews and documentation. Thirteen informants, comprising 10 MSME owners, 1 local official, 1 religious affairs officer, and 1 policymaker, were selected through snowball sampling. The findings reveal that while most MSME owners view halal certification as both a religious obligation and a business strategy, many face difficulties in navigating the certification process due to a lack of knowledge and support from the government. These results suggest the need for targeted education, streamlined procedures, and institutional support to improve halal compliance and enhance MSME competitiveness.